METHODICAL CONCEPTS OF MONITORING MODEL IN GENERAL SECONDARY EDUCATION SYSTEM - Vakhobov, M.M. (ILIM hám JÁMIYET, 2016)
In the article there are discussed the issues of knowledge assessment and student’s competence, the principles forming assessment, monitoring development tendencies and education quality assessment in general secondary education system in Uzbekistan and modeling issues of monitoring system.